Ang Darling kong Aswang - Sotto, Vic; Reyes, Cristine; Rivero, Dante; Ramos, Wendell
Eliza (Cristine Reyes) is the kind of aswang who is reluctant in eating human flesh. When Joaquin (Refael Rosell), a wicked aswang pressures her into marrying him or she and her mother Ida (Agot Isidro) will face tragic consequences, Eliza escapes to the city where a widower named Victor (Vic Sotto) lives. Victor keeps his distance from women, focusing only on his two daughters, but this changes when he meets Eliza. They eventually become sweethearts. Eliza also tells Victor about her true identity, but this does not stop Victor from marrying her. Their bliss, however, is short-lived as Joaquin has captured Ida, forcing Eliza to leave Victor to save her mother. But Victor discovers something about himself, which could help bring Eliza back to him.